2003
DOI: 10.1212/01.wnl.0000083991.81859.73
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical blood flow effects of subthalamic nucleus stimulation in PD

Abstract: These data suggest that STN stimulation increases firing of STN output neurons, which increases inhibition of thalamocortical projections, ultimately decreasing blood flow in cortical targets. STN stimulation appears to drive, rather than inhibit, STN output neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
132
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 21 publications
21
132
1
1
Order By: Relevance
“…Discrete metabolic reductions in motor cortical and cerebellar areas distant from the stimulation site have been reported with STN DBS (Hershey et al, 2003;Hilker et al, 2004;Payoux et al, 2004). Our data are compatible with the notion of CSPTC hyperactivity in resting PD patients, which may be reduced by stimulation.…”
Section: Metabolic Changes With Stn Stimulationsupporting
confidence: 91%
“…Discrete metabolic reductions in motor cortical and cerebellar areas distant from the stimulation site have been reported with STN DBS (Hershey et al, 2003;Hilker et al, 2004;Payoux et al, 2004). Our data are compatible with the notion of CSPTC hyperactivity in resting PD patients, which may be reduced by stimulation.…”
Section: Metabolic Changes With Stn Stimulationsupporting
confidence: 91%
“…The relative importance of inhibitory GPe-GPi connections compared to excitatory STN-GPi connections in nonparkinsonian subjects (see the 1995 article by Calon et al, 42 for example) stimulated with small electrodes and long pulses may have contributed to the observed differences. Positron emission tomography (PET) experiments in humans have confirmed that blood flow in the region of GPi increases during STN HFS, 43 which is consistent with activation of output from the stimulated site. A functional MRI study also found an increase in blood oxygen level-dependent signal in GPi of patients undergoing STN HFS.…”
Section: Axonal Output Of the Stimulated Nucleusmentioning
confidence: 75%
“…These studies have resulted in general guidelines on the selection of stimulation parameters, as well as clinical algorithms for programming the devices. Imaging studies have developed correlations between stimulation parameters and markers of brain activity (Hershey et al, 2003;Haslinger et al, 2005;Phillips et al, 2006;Trost et al, 2006), and identified the location of therapeutic DBS electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). Modeling studies have characterized the theoretical effects of DBS electric fields on the underlying neural tissue (McIntyre et al, 2004b;Miocinovic et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%